Wavelength Demultiplexer using Heterostructure Ring Resonators in Triangular Photonic Crystals - Mohammad Reza Rakhshani; Moahmmad Ali Mansouri-Birjandi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this Paper a new type of wavelength demultiplexer using ring resonators in 2D triangular photonic crystal is presented. The designed demultiplexer contents two regions which each own a resonator. Two dielectric constants are used in this demultiplexer. These structures which are called hetero have the capability to be used in wavelength division multiplexing (WDM) systems. The average transferred power for the two output channels is about 93%. The crosstalk between output channels was more than -18.5dB, also the overall size of the structure was about 144µm2 which is so appropriate for fabrication and integration. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2331